Metabolic and functional responses playing tennis on different surfaces - Murias, J. M.; Lanatta, D.; Arcuri, C. R.; Laino, F. A. (The Journal of Strength and Conditioning Research, 2007)
The purpose of this study was to compare various metabolic and functional responses while playing tennis on clay and hard courts. Twelve 90-minute matches were played (6 on clay courts and 6 on hard courts) by 4 nationally ranked players. During the on-court tests, oxygen uptake (VO2) and heart rate (HR) were measured using portable systems. Capillary blood lactate concentration (LA) was measured every 10 minutes. Additionally, distance ran, playing time, resting time, and exercise to rest ratio were monitored by time-motion analysis. The statistical analysis showed that playing time was higher on clay courts than on hard courts (p < 0.05), and resting time on clay courts and hard courts was not statistically different (p > 0.05). The exercise to rest ratio was affected by the interaction between playing time and resting time, showing a longer recovery time per unit of exercise on hard courts than on clay courts (p < 0.05). Distance ran, mean HR, and mean LA were significantly higher on clay courts than on hard courts (p < 0.05). There was less fluctuation of the VO2 response on clay courts than on hard courts. Therefore, it is suggested that conditioning programs should be adjusted according to the playing surface to account for the longer playing time, greater exercise to rest ratio, increased HR and LA, and a more steady pattern of VO2 seen on clay courts.